ARE THUMB INJURIES BECOMING MORE FREQUENT IN MEN'S LACROSSE?. Issue 17 (24th October 2013) - Webb, M; Hoskins, T; Price, J
Abstract : Men's lacrosse is a rapidly growing sport. The authors were concerned by the number of thumb injuries sustained while working with an international team at the 2012 European Championships. To compare data collected during immediate pre-tournament training camp and the European Championships with published reports. Data was gathered prospectively on all 23 players on the England Men's lacrosse team. An injury was defined as one that occurred during a team practice or game, and resulting in the player missing one or more further sessions. Over 15 days, 23 players participated in 17 athletic exposures each. This included 9 games and 8 practices. There were 3 thumb injuries (Rate=0.007673). 1 occurred from contact with an opponent, 1 from direct contact with an opponent's stick and another from a direct blow from the ball. 2 fractures of the proximal phalanx and 1 MCPJ sprain. The data was compared with published by Bowers et al . 1 They reported 276 thumb injuries in 1, 019, 222 athletic exposures (Rate=0.000271). A c2 test with Yates correction for continuity was performed. This yielded a Yates' c2 value of 53.559 which is statistically significant (p<0.001). Mechanism of injury corroborates with published reports. Lacrosse has become more popular and there has been a trend to develop lighter flexible equipment. Data needs to be collected to determine if thumb injuries can be attributed to equipment design. We would advise manufacturers to explore alternative designs to help protect the thumb more successfully.